Molecular Mechanism of Berberine in the Treatment of Calcified Aortic Valve Disease Based on AGE-RAGE Signal Pathway - Xiao, Han; Xie, Li; Ma, Yili; Fu, Shilin; Guo, Maoyang; Qian, Dehui (Alternative therapies in health and medicine, 2023)
Objective * We aimed to explore the molecular mechanism of berberine in the treatment of calcified aortic valve disease through the network pharmacology-molecular docking method. Methods * The targets of berberine and calcified aortic valve disease were retrieved, the interactions between the targets were analyzed, Cytoscape software was used to build a "target-path" network, R language was used to conduct enrichment analysis of GO and KEGG pathways, and AutoDock Vina was used to verify the binding force of the target protein and small molecules. Results * 96 targets for berberine and 4293 disease targets were screened through multiple databases, and 56 targets were identified through veen analysis. The enrichment of PPI, GO, and KEGG pathways suggests that berberine may act on PIK3CD, PIK3CB, PIK3R1, MAPK14, MAPK10, and other targets, and regulate the role of calcified aortic valve disease through AGE-RAGE signaling pathway, Chemokine signaling pathway, Lipid and atherosclerosis, and other pathways. The docking results showed that berberine has good binding activity with the target on the key pathway AGE-RAGE signaling pathway. Conclusion * The network pharmacology preliminarily revealed the mechanism of berberine in the treatment of calcified aortic valve disease by regulating vascular calcification, inflammatory reaction, oxidative stress, and other effects, providing the basis for follow-up experimental research, and also providing the basis for clinical medication. (Altern Ther Health Med. 2023;29(8):42-47)